2000
DOI: 10.1097/00002341-200001000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Seasonal Variation in Graves Disease

Abstract: This study fails to provide evidence for a seasonal influence on the incidence of Graves disease and the associated orbitopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Seasonal variation has been observed in several retrospective studies of Graves’, 3,20,21 but not in others 19,22 . No obvious variation was highlighted by graphing the data, and χ 2 analysis did not show a significant difference in the months.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Seasonal variation has been observed in several retrospective studies of Graves’, 3,20,21 but not in others 19,22 . No obvious variation was highlighted by graphing the data, and χ 2 analysis did not show a significant difference in the months.…”
Section: Discussionmentioning
confidence: 79%
“…19 Seasonal variation has been observed in several retrospective studies of Graves', 3,20,21 but not in others. 19,22 No obvious variation was highlighted by graphing the data, and v 2 analysis did not show a significant difference in the months. However, subtle seasonal variation may be uncovered in larger surveys by means of more complex analysis than this.…”
Section: Hashimoto's or Graves' Disease?mentioning
confidence: 93%
“…[1][2][3][4] It commonly affects women in the fifth decade of life and is usually diagnosed soon after the glandular aspects of Graves disease appear. 2,[5][6][7] Components of the orbital process include symmetric soft tissue swelling, proptosis, lid retraction (with characteristic temporal flare), and strabismus, due in large part to fibrosis of the extraocular muscles ( Figure 1 and Figure 2). The self-limited disease requires only supportive measures except in cases where severe corneal exposure keratitis or compressive optic neuropathy threatens vision and requires immediate medical attention.…”
Section: Clinical Features Of Taomentioning
confidence: 99%
“…Whereas in 80% of patients the onset of the glandular and orbital diseases occurs within 18 months of each other, the clinical appearance of the two can be separated by as much as 20 years in some cases. [5][6][7] Unlike other autoimmune diseases that are typically chronic with unpredictable episodes of acute relapse, most patients with TAO undergo spontaneous remission within 18 months of disease onset. This resolution does not appear to vary according to the type of therapy used.…”
Section: Some Unanswered Questionsmentioning
confidence: 99%
“…Whereas some authors reported an increased occurrence in the warmer months of the year [8,9], others failed to find any significant difference between seasons [10,11]. This discrepancy could be partly due to a bias toward increased awareness of thyrotoxic symptoms on warmer days [8] in addition to the effect of differing amounts of iodine in the diet [9].…”
mentioning
confidence: 99%